Insights Into the Role of Mitochondria in Vascular Calcification - Zeng, ZL; Yuan, Qing; Zu, Xuyu; Liu, Jianghua (Frontiers in Cardiovascular Medicine, 2022)
Vascular calcification (VC) is a growing burden in aging societies worldwide, and with a significant increase in all-cause mortality and atherosclerotic plaque rupture, it is frequently found in patients with aging, diabetes, atherosclerosis, or chronic kidney disease. However, the mechanism of VC is still not yet fully understood, and there are still no effective therapies for VC. As energy metabolism factories, mitochondria play a crucial role in maintaining vascular physiology. Discoveries in past decades signifying the role of mitochondrial homeostasis in normal physiology and pathological conditions led to tremendous advances in the field of VC. Therapies targeting basic mitochondrial processes, such as energy metabolism, damage in mitochondrial DNA, or free-radical generation, hold great promise. The remarkably unexplored field of the mitochondrial process has the potential to shed light on several VC-related diseases. This review focuses on current knowledge of mitochondrial dysfunction, dynamics anomalies, oxidative stress and how it may relate to VC onset and progression and discusses the main challenges and prerequisites for their therapeutic applications.